Fear of Falling and Moderate-to-Vigorous Physical Activity in Community-Dwelling Older Adults. A Cross-Sectional Analysis - Kanavaki, Archontissa; Michalopoulou, Maria; Kouli, Evgenia; Gkrekidis, Athanasios; Douda, Helen; Smilios, Ilias; Gourgoulis, Vasilios; Sirakoulis, Georgios; Aggelousis, Nikolaos (Inquiries in Physical Education and Sport, 2023)
Physical activity guidelines for older adults include at least 150min of moderate-to-vigorous aerobic physical activity (MVPA) per week. Fear of falling (FoF) is common among community-dwelling older adults and can lead to activity restriction in daily living and in turn increased fall risk. Given the limited evidence linking FoF with accelerometer-assessed MVPA, the present study aimed to examine the association of FoF with MVPA controlling for key confounders, including physical function, falls history and unsteady gait. A total of 149 community-dwelling individuals ≥60 years (mean age=72.10±6.23, 84.6% women) completed a set of self-report and physical performance measures and wore a triaxial accelerometer for a week. Multivariate linear regression models examined the association between FoF and MVPA adjusting for potential confounders. In the fully adjusted model, 28.2% of the variance in MVPA was explained by the predictors (Fchange=4.97, p<.01) and high FoF was significantly associated with less minutes/week of MVPA (β=-12.33, BCa CIs[-19.89, -4.32]). Findings revealed that among the multiple sources associated with MVPA in older adults, FoF has a small, yet significant influence. Identifying individuals with high FoF and addressing these concerns, should be part of the encounters exercise and other professionals have with older adults, as this could promote a more active lifestyle and reduce fall risk in this population.